POTENTIAL OF EMISSION FOURIER TRANSFORM INFRARED SPECTROSCOPY FOR IN SITU EVALUATION OF KEROGEN IN SOURCE ROCKS DURING PYROLYSIS - Marshall C.P.; Wilson M.A.; Hartung-Kagi B.; Hart G. (My University, 2001)
Eleven petroleum source rock samples have been examined by Emission Fourier transform infrared spectroscopy (FTIRES) and by Rock-Eval thermal analyses. FTIRES has been used to estimate the amount of C-H aliphatic and C-H aromatic signal lost during thermal treatment at Rock-Eval temperatures. In particular, the loss of signal from 150°C to 300°C has been monitored and compared to the yield of oil obtained over this range by Rock-Eval analysis. Likewise, signal loss between 300-500°C and 500-700°C was monitored. Correlations of FTIRES changes with Rock-Eval pyrolysis derived parameters were not found because FTIRES reflects changes in composition of undistilled material during pyrolysis. However, by relating Rock-Eval and FTIRES derived parameters a source rock quality index can be derived. This index can be useful as a quick routine method for scanning samples to determine if the free oil in the source rock was generated by thermal maturation of the same source rock.
Keywords: KEROGEN; PYROLYSIS; INFRARED SPECTROSCOPY; SOURCE ROCKS; PETROLEUM